2011
DOI: 10.1128/iai.00808-10
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CCR2+Gr1+Cells Control Growth of theYersinia pestisΔyopMMutant in Liver and Spleen during Systemic Plague

Abstract: We are using a systemic plague model to identify the cells and pathways that are undermined by the virulence protein YopM of the plague bacterium Yersinia pestis. In this study, we pursued previous findings that Gr1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 63 publications
4
53
0
Order By: Relevance
“…1E). These results are consistent with the recent observation of trans-complementation occurring in the spleens (but not the livers) of mice inoculated intravenous with Y. pestis KIM5 (pgm − ) and an isogenic ΔyopM mutant (15). Although trans-complementation following subcutaneous or intravenous infection are not as pronounced as that seen during pulmonary coinfection, all of these results suggest a dominant immunosuppressive effect of wild-type bacteria and demonstrate that the physiology of different organ systems may determine the extent of trans-complementation.…”
Section: Resultssupporting
confidence: 81%
“…1E). These results are consistent with the recent observation of trans-complementation occurring in the spleens (but not the livers) of mice inoculated intravenous with Y. pestis KIM5 (pgm − ) and an isogenic ΔyopM mutant (15). Although trans-complementation following subcutaneous or intravenous infection are not as pronounced as that seen during pulmonary coinfection, all of these results suggest a dominant immunosuppressive effect of wild-type bacteria and demonstrate that the physiology of different organ systems may determine the extent of trans-complementation.…”
Section: Resultssupporting
confidence: 81%
“…Both the yopE and yopK mutants have been shown previously to reach MLNs before being cleared (20,25,42), but not at the early time points observed here in the absence of PMNs. These findings are in accordance with those of previous studies using PMN-depleted mice, showing that Y. pseudotuberculosis yopK and yopH mutants, and also Y. pestis yopM mutants, have higher infectious capacities in the absence of PMNs (20,37,38).…”
Section: Discussionsupporting
confidence: 83%
“…In a recent study, we showed that depletion of Gr-1 ϩ cells enables the otherwise avirulent Y. pseudotuberculosis yopK mutant to cause systemic infection in mice (20). Further, Y. pestis grows better in the spleen and liver upon depletion of Gr-1 ϩ cells, and a Y. pestis yopM mutant is more virulent after depletion of either Gr-1 ϩ or Ly6G ϩ cells (37,38). However, the effects of PMN depletion on early infection have not been investigated previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…opM plays a dominant role in the infection processes of different Yersinia strains in different host organs (1)(2)(3)(4). The yopM gene sequence was first reported for Yersinia pestis strain KIM5, and subsequently the encoded protein was demonstrated to be a possible virulence factor that mimicked the host homolog human platelet glycoprotein 1b (GPI␣) and influenced platelet aggregation (5-7).…”
mentioning
confidence: 99%